SIFAT FISIK DAN MEKANIK PAPAN PARTIKEL DARI SERBUK GERGAJIAN KAYU SENGON LAUT (Paraserianthes falcataria) MENGGUNAKAN PEREKAT PVAC - Hendra Mirza; Muhammad Faisal Mahdie; Gusti Ahmad Rahmat Thamrin (Universitas Lambung Mangkurat, 2020)
The purpose of this study is to analyze the physical and mechanical properties of the particle board of sengon wood powder (Paraserianthes falcataria) using PVAC adhesives and to analyze the suitability of wood as raw material for particle board. The method used is physical properties testing in the form of testing water content and density as well as testing mechanical properties in the form of flexural strength (MoE) and fracture firmness (MoR). The physical properties of the particle board with the addition of different adhesives between 1.0.54-1.0.63 grams each treatment did not significantly affect the value of water content. Overall average water content reaches less than 14% that has met SNI, each treatment has no significant effect on the density value, the density value meets the Indonesian National Standard (SNI) with SNI requirements for particle board density of 0.4-0.9 gr / cm3 (low density), the average modulus of elasticity (MoE) produced had a very significant effect and fulfilled the SNI for particle board min 20400 kgf / cm2 in A2 treatment, but did not meet the standards in A1 and A3 treatments, the average value of fracture constancy (MoR) for each treatment has a very significant effect and according to the standards set SNI min 82 kgf / cm2 already meets the standard in A2 treatment with a ratio between powder and adhesive 1: 0.58 while it does not meet the standard in treatment A1 , and A3. The suitability of Sengon wood powder (Paraserianthes falcataria) to the physical and mechanical properties of the particle board in the form of water content, density, flexural strength (MoE) and fracture firmness (MoR) for each given treatment is appropriate because most have met the Standard Indonesian National (SNI).Keywords: Particle Board, Physical Properties, Mechanical Properties